Lime and mycorrhizae in the phosphorus deficiencies correction in an andisol cultivated with Pinus halepensis Mill. - Álvarez-Sánchez, María E.; Hernández-Acosta, Elizabeth; Maldonado-Torres, Ranferi; Rivera-González, Miguel (Instituto de Ecología, A.C., 2013)
In order to evaluate soil liming and the potential of inoculation of a multistrain with propagules of arbuscular mycorrhizal fungi (AMF) in the development and accumulation of P. halepensis Mill phosphorus, grown in an Andisol, it was evaluated, in a greenhouse, the application of lime to raise the soil pH from 5,3 to 5,5; 6,0 and 6,5; with and without the addition of mycorrhizae. The results showed that mycorrhizal inoculation and the soil liming to pH of 6,0 to 6,5; led to a further development of seedling, measured in dry aerial weight, stem diameter, height, and root volume, as well as phosphorus accumulation by plants, compared with the control (with no agricultural liming and without inoculation with AMF). Liming stimulated the percentage of colonization, regardless inoculation with AMF. The field validation of the liming treatment to pH 6,5 and AMF inoculation promoted 95% survival of trees with an average increase in height and stem diameter of 22,1 cm and 5 cm, respectively, during an evaluation period of five months. The greenhouse and field results suggest the benefits of liming and inoculation with arbus cular mycorrhizal as effective practices for the commercial establishment of P. halepensis in Andisols in the state of Mexico.